GENETIC AND NUTRITIONAL PROFILING OF COMMON BEAN (PHASEOLUS VULGARIS L) GERMPLASM FROM AZAD JAMMU AND KASHMIR AND EXOTIC ACCESSIONS - S. Jannat; A. H. Shah; K. N. Shah; S. Kabir; A. Ghafoor (Journal of Animal and Plant Sciences, 2019)
Common bean (Phaseolus vulgaris L.) is an important legume around the globe and major crop in Jammu and Kashmir after maize and wheat. Despite of its consumption and importance, the farmers are deprived of any improved cultivar and very little attention has been given to the crop for genetic improvement in Pakistan. The exploitation, utilization and conservation of indigenous gene pool and its comparison with exotic germplasm have a very significant role for sustainable nutritional requirements of the mountain communities. The most important bean growing areas of Azad Jammu and Kashmir were selected for germplasm collection. Protein fingerprinting through SDS-PAGE along with nutritional and morphological profiling of the collected germplasm and it comparison with the exotic accessions was performed. Among the seed characteristics, seed coat color and seed shape were found the most diverse attributes while all studied morphological characters showed highly significant variability with accession Lipa-1 as most diverse among all. Similarly evidences from biochemical profiling revealed significant variation with highest protein contents in Neelum-1, i.e. 26%.  The accession Lipa-4 showed less cooking time i.e. 79 minutes. Significant molecular diversity on the basis of seed storage protein was evaluated using SDS-PAGE. Similarly the accession Rawalakot has been found rich in protein content, promising in yield and maturity time hence is recommended for general cultivation. Genetically diverse pattern in common bean accessions provided a base for comprehensive breeding program in Pakistan and AJK in future and recommended local accession will help in diversification of conventional agriculture system.
Keywords: Biochemical Profiling; Exotic; Germplasm; Indigenous; Genetic Diversity; SDS-PAGE; Significant.